Effect of Biofermentation Duration of Chromolaena odorata with Liquid Palm Sugar as A Carbon Source on Content and in vitro Digestibility of Crude Protein and Crude Fiber - Ratu, Hilda Anggriani; Dato, TwenfoTwenfosel O. Dami; Lestari, Gusti Ayu Yudiwati (Jurnal Biologi Tropis, 2026)
This study aimed to evaluate the effect of biofermentation duration of Chromolaena odorata using liquid palm sugar as a carbon source on crude protein content, crude fiber content, and the in vitro digestibility of crude protein and crude fiber. The experiment employed a Completely Randomized Design (CRD) consisting of four treatments and four replications, resulting in 16 experimental units. The treatments were biofermentation for 0 days (LB-0), 7 days (LB-7), 14 days (LB-14), and 21 days (LB-21, control). The observed parameters included crude protein content, crude fiber content, in vitro digestibility of crude protein, and in vitro digestibility of crude fiber. Data were analyzed using analysis of variance (ANOVA). The results showed that biofermentation duration significantly affected (P<0.05) crude fiber content and in vitro crude fiber digestibility but had no significant effect (P>0.05) on crude protein content or in vitro crude protein digestibility. The lowest crude fiber content (17.55%) and the highest in vitro crude fiber digestibility (17.88%) were obtained after 7 and 14 days of biofermentation, respectively. Overall, biofermentation using liquid palm sugar effectively reduced crude fiber content and improved crude fiber digestibility, with 7 days identified as the optimal biofermentation duration. However, this treatment did not improve crude protein content or in vitro crude protein digestibility.